Awareness of Responsible Citizenship Components among Primary Schoolgirls in Jeddah: أ.د. إيمان سالم أحمد بارعيده , شروق أحمد فيصل المالكي (Journal of the College of Education for Women, 2021)
The research examines the awareness of the components of responsible citizenship among primary schoolgirls in Jeddah using a descriptive approach. A test was then prepared, which consists of loyalty, affiliation to homeland, conscious citizenship based on the knowledge of rights, the fulfillment of duties, family roles in education and society revival, homeland and preservation of the components and gains, participation in achievements, and of national heritage. To maintain the validity and reliability of the study, 28-item test of multiple-choice and short essays type was applied to a random sample of (303) female students in the (fourth-fifth-sixth) primary school class in Jeddah. Results have shown that the level of awareness of school-grade students (fourth-fifth-sixth) of the components of responsible citizenship as a whole was high, where the means of the components ranged between (0.71-0.86). Moreover, the highest mean for the component (family and strengthening its vital tools in education and community development) was (0.86). Results have further shown that there are statistically significant differences between the averages. The mean of the responsible citizenship test according to the grade variable has a test value that is equal to (123.16). That is, there is a statistically significant value at the level of (0.05 α≤). Besides, there are statistically significant differences between the means for the fourth and fifth grades in favor of the fifth grade, and between the means of the fourth and sixth grades in favor of the sixth grade. Finally, there are no statistically significant differences between the means of the fifth and sixth grades.